Optimalisasi Pengendalian Smart Home Melalui Teknologi Prototipe Hand Tracking dan Speech Recognition - Leovander Aditama Syahputra; Fachry Rizky Prasetya; Abhinaya Fahar Laila (Repeater : Publikasi Teknik Informatika dan Jaringan, 2025)
This study aims to develop an intuitive and efficient smart home control system by utilizing hand tracking and speech recognition technologies. These technologies employ the OpenCV, Mediapipe, PyAudio, and Speech Recognition libraries to recognize hand gestures and voice commands in real-time. The system is developed using a Raspberry Pi connected to a webcam and microphone as input devices, and a relay to control electronic appliances. The results show a high accuracy rate at optimal light intensity for hand tracking and a specific distance for speech recognition. This system is implemented in an IoT environment to control devices such as lights and door locks. The research is expected to contribute to the development of smarter and more user-friendly smart homes.